Experimental and numerical analyses of fluid flow inside additively manufactured and smoothed cooling channels. (June 2022) - Favero, G.; Berti, G.; Bonesso, M.; Morrone, D.; Oriolo, S.; Rebesan, P.; Dima, R.; Gregori, P.; Pepato, A.; Scanavini, A.; Mancin, S.
Abstract: The surface roughness can be considered one of the main drawbacks of the Laser Powder Bed Fusion (LPBF) technology applied to thermal applications. Favero et al. [1] experimentally and numerically demonstrated that the surface roughness of printed copper channels deeply affects their fluid dynamic performance and limits the predictive capabilities of the CFD tools. The authors proposed a methodology to calibrate the numerical tools in turbulent flow. However, the problem remains unsolved because the printed copper channels exhibit remarkably higher pressure drops when compared to conventional smooth channels, hindering the proper deployment of the technology in the thermal sector. This paper proves how it is possible to smooth the internal walls of channels obtained via LPBF to reduce the surface roughness. In fact, the chemical milling process is proposed and applied. The smoothed channels showed a fluid dynamic behaviour similar to the conventional ones. Finally, by coupling Computer Tomography to the CFD tool, the fluid dynamic behaviour inside the smoothed channels is fairly predicted, confirming that the surface roughness and the channel dimensions are the controlling parameters of the fluid dynamic performance of channels printed via LPBF.